Flexible anodic bonding for the bonding between elastomer and metal. Issue 33 (24th June 2022) - Zhao, Haocheng; Liu, Cuirong; Du, Chao; Zhang, Ying; Zhang, Zhichao; Liang, Chunping; Wu, Yuling
Abstract: Considering the inadaptability of traditional anodic bonding to polymer materials, the flexible anodic bonding process is developed. The bonding characteristics of the dynamic intelligent electric fields with the low‐temperature plasma surface treatment to polymer and ultrasonic‐assisted preconnection before bonding are very suitable for the anodic bonding of polymer elastomer to aluminum (Al) sheet. A series of composite polyurethane elastomer cathode materials (CPECs) with good bonding properties are prepared and characterized. The highest ionic conductivity of CPECs can reach to 2.7 × 10 −3 S/cm (CPEC2) at 75°C. After bonded, it is determined that a uniform and dense intermediate bonding layer showed by SEM is formed between CPECs and Al. In addition, different elements including C, O, F, S, and Al are clearly identified by EDS in the bonding layers, showing that the process of flexible anodic bonding has accompanied the directional migration of ions. The maximum tensile strength of bonding layer for CPEC2 and Al (CPEC2‐Al) is up to 2.03 MPa. It is proven that the developed flexible anodic bonding can effectively improve the joint quality and reliability for polymer elastomer materials. All these results of anodic bonding are more potentially valuable to the packaging of flexible devices. Abstract : In order to improve the success rate of anodic bonding for polymer materials, the flexible anodic bonding process characterized by the dynamic intelligent electric fields, low‐temperature plasma surface treatment to polymer materials, and ultrasonic‐assisted pre‐connection before connection has been developed. Meanwhile, a series of composite polyurethane elastomer packaging materials (CPECs) with good bonding properties are prepared and characterized. What it means that it provides a possibility for packaging of flexible MEMS device to use anodic bonding technology.